The Role of Lipids in Allergic Sensitization: A Systematic Review - Hopkins, Georgina V.; Cochrane, Stella; Onion, David; Fairclough, Lucy C. (Frontiers in Molecular Biosciences, 2022)
Background Immunoglobulin E (IgE)-mediated allergies are increasing in prevalence, with IgE-mediated food allergies currently affecting up to 10% of children and 6% of adults worldwide. The mechanisms underpinning the first phase of IgE-mediated allergy, allergic sensitization, are still not clear. Recently, the potential involvement of lipids in allergic sensitization has been proposed, with reports that they can bind allergenic proteins and act on immune cells to skew to a T helper type 2 (Th2) response. Objectives The objective of this systematic review is to determine if there is strong evidence for the role of lipids in allergic sensitization. Methods 19 studies were reviewed, 10 of which were relevant to lipids in allergic sensitization to food allergens, 9 relevant to lipids in aeroallergen sensitization. Results The results provide strong evidence for the role of lipids in allergies. Intrinsic lipids from allergen sources can interact with allergenic proteins to predominantly enhance but also inhibit allergic sensitization through various mechanisms. Proposed mechanisms included reducing the gastrointestinal degradation of allergenic proteins by altering protein structure, reducing dendritic cell (DC) uptake of allergenic proteins to reduce immune tolerance, regulating Th2 cytokines, activating invariant natural killer T (iNKT) cells through CD1d presentation, and directly acting upon toll-like receptors (TLRs), epithelial cells, keratinocytes, and DCs. Conclusion The current literature suggests intrinsic lipids are key influencers of allergic sensitization. Further research utilising human relevant in vitro models and clinical studies are needed to give a reliable account of the role of lipids in allergic sensitization.